Processing speed test: Validation of a self-administered, iPad®-based tool for screening cognitive dysfunction in a clinic setting. (December 2017) - Rao, Stephen M; Losinski, Genna; Mourany, Lyla; Schindler, David; Mamone, Bernadett; Reece, Christine; Kemeny, Danielle; Narayanan, Sridar; Miller, Deborah M; Bethoux, Francois; Bermel, Robert A; Rudick, Richard; et al.
Background: Cognitive dysfunction is common in multiple sclerosis (MS) patients and has important consequences for daily activities, yet, unlike motor function, is not routinely assessed in the clinic setting. We developed the Processing Speed Test (PST), a self-administered iPad ® -based tool to measure MS-related deficits in processing speed. Objective: To determine whether the PST is valid for screening cognitive dysfunction by comparing it to the paper-and-pencil Symbol Digit Modalities Test (SDMT). Methods: We assessed PST test–retest reliability, sensitivity of PST and SDMT in discriminating MS patients from healthy controls (HC), convergent validity between PST and SDMT, correlations between T2 lesion load and PST and SDMT, and PST performance with and without technician present during administration. Results: PST had excellent test–retest reliability, was highly correlated with SDMT, was slightly more sensitive than SDMT in discriminating MS from HC groups, and correlated better with cerebral T2 lesion load than did SDMT. Finally, PST performance was no different with or without a technician in the testing environment. Conclusion: PST has advantages over SDMT because of its efficient administration, scoring, and potential for medical record or research database integration. PST is a practical tool for routine screening of processing speed deficits in the MS clinic.